Comprehensive assessment of the quality of life in patients with pelvic organ prolapse before surgical treatment: A prospective cohort observational study - Rustam A. Shakhaliev; Nikita D. Kubin; Tatiana P. Nikitina; Tatyana I. Ionova; Dmitry D. Shkarupa (IP Berlin A.V., 2024)
Aim. To evaluate comprehensively the quality of life (QoL) of patients with pelvic organ prolapse (POP) who have indications for reconstructive surgery (RS) and determine the optimal tools for QoL assessment as part of preoperative screening. Materials and methods. The study included 860 patients hospitalized for RS at the Saint-Petersburg State University Hospital. The following validated questionnaires were used to assess QoL: the RAND SF-36 (general QoL questionnaire and specialized questionnaires), in particular the P-QoL (QoL Pelvic Organ Dysfunction Questionnaire in POP), the PFDI-20 (Pelvic Organ Dysfunction Questionnaire), the ICIQ-SF (Stress Incontinence Questionnaire), the PISQ-12 (PTD Sexual Dysfunction Questionnaire), the HADS (Hospital Anxiety and Depression Scale). Lower abdominal and lower back pain was assessed using a Visual Analog Scale. Results. Significant QoL reduction was found in most patients, including in physical and psycho-emotional aspects. Among the patients, there were no women with a high level of physical and mental health components. The indicators of vitality, general health, role-physical, and emotional functioning were more significantly reduced. More than 1/3 of women had borderline or increased levels of anxiety, and 1/4 had high levels of depression. Notably, the P-QoL questionnaire was used for the first time in the russian population of patients with POP. It identifies general health perceptions, the impact of prolapse on life, role, physical, social and personal limitations, emotions, sleep/energy, and symptom severity. Based on the study, optimal tools for preoperative screening and monitoring the state of patients after surgery are proposed. Conclusion. The population of women with POP with indications for RS is heterogeneous in terms of the severity of physical and psychosocial functioning impairment and the degree of impact of pelvic organ prolapse symptoms. The following questionnaires can be considered as optimal tools for assessing QoL and symptom burden in patients with POP as part of preoperative screening: P-QoL to assess the decrease of various QoL aspects, PFDI-20 to determine the severity of specific pelvic organ dysfunction symptoms, HADS to identify the level of anxiety and depression.